2018
DOI: 10.1002/slct.201702848
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Bronsted‐Lewis Acidity Effect on Upgrading Biomass‐Derived Phenolic Compounds: Statistical Optimization of Process Parameters, Kinetic Investigations and DFT Study

Abstract: Biomass‐derived phenolic compounds and small oxygenates obtained from pyrolysis of lignocellulosic biomass needs to be upgraded to obtain the C10‐C13 range fuel precursors. In this context, iso‐propylation of m‐cresol was performed in batch reactors using multifunctional ionic liquids (ILs) as catalysts. Environmentally benign Bronsted‐Lewis acidic ILs were synthesized and characterized using 1H NMR, 13C NMR and Raman spectroscopic data. Relative Bronsted and Lewis acidity of these ILs were compared using UV‐V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In contrast to the findings of O'Connor et al, the authors reported preferred formation of the O‐alkylated product over H‐ZSM‐5 zeolite. Other reports for the alkylation of m ‐cresol with medium selectivity can be found for catalysts like H‐BEA zeolite, 24,27,31 ZnAl 2 O 4 , 32 ionic liquids, 33,34 sulphated ZrO 2 ‐TiO 2 , 35 (sulphated) Al 2 O 3 , 36 heterogenized AlCl 3 , 37 Fe 2 O 3 38 and magnesium‐aluminium hydrotalcites 39 (Table 2).…”
Section: Symrise: Menthol From M‐cresol and Propenementioning
confidence: 96%
“…In contrast to the findings of O'Connor et al, the authors reported preferred formation of the O‐alkylated product over H‐ZSM‐5 zeolite. Other reports for the alkylation of m ‐cresol with medium selectivity can be found for catalysts like H‐BEA zeolite, 24,27,31 ZnAl 2 O 4 , 32 ionic liquids, 33,34 sulphated ZrO 2 ‐TiO 2 , 35 (sulphated) Al 2 O 3 , 36 heterogenized AlCl 3 , 37 Fe 2 O 3 38 and magnesium‐aluminium hydrotalcites 39 (Table 2).…”
Section: Symrise: Menthol From M‐cresol and Propenementioning
confidence: 96%
“…Moreover, the valorization process is carbon-waste free and also has tremendous potential to produce, exclusively, fuel range components without any industrial waste. In this context, the C–C alkylation reaction between phenolic compounds and small oxygenates such as alcohols has become a highly significant industrial reaction. , Furthermore, the alkylated phenolic compounds obtained in this process are used in the paint, rubber, pharmaceutical, and cosmetics industry as fine chemicals. Alkylation of m- cresol with iso -propanol has been considered one such industrially important model reaction to demonstrate the efficient production of C 10 -C 13 range fuel precursors. , The desired product is mainly 2- iso -propyl-5-methyl phenol (IMP), also known as thymol, used widely in fuels, food packaging, pharmaceuticals, rubber, and the paint industry. , Several side products such as benzene ring side-chain isomers of thymol, ether, dialkylated products, iso- butylated products, and thermally isomerized as well as dehydrated products from alcohol are also formed in significant amount in this reaction under different reaction conditions.…”
Section: Introductionmentioning
confidence: 99%